The Effect of Peer Tutor Method on Writing Skills of Fifth Grade Elementary School Students: Pengaruh Metode Tutor Teman Sebaya Terhadap Keterampilan Menulis Siswa Kelas V SD - Dharma Satria Wijaya (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this research is to describe writing skills in learning activities from home during the covid-19 pandemic at SD Negeri Lemah Putro 1 Sidoarjo and to describe the obstacles faced by teachers in implementing learning activities from home during the COVID-19 pandemic in elementary schools. Negri Lemah Putro 1 Sidoarjo, Data analysis was carried out using the Miles and Haberman model. The results showed that peer tutors in learning activities from home during the covid-19 pandemic at SD Negeri Lemah Putro 1 Sidoarjo were seen in the learning planning, implementation, and assessment of learning that had an effect on students who would further improve their learning. The results also showed that the obstacles faced by teachers in learning activities from home during the covid-19 pandemic at SD Negeri Lemah Putro 1 Sidoarjo were signal problems and parents who paid less attention to their children's tasks because they were busy working.